eiraszero11cu

2021-12-23

How do you solve for y: $2x-3y=6$ ?

user_27qwe

Skilled2021-12-30Added 230 answers

Let us proceed to solve the equation 2x - 3y = 6
We take the term 3y to the right-hand side of the equation which gives 2x = 6 + 3y
Now we bring 6 to the left side of the equation 2x - 6 = 3y
And lastly, we bring the 3 also to the other side of the equation thus dividing the term (2x-6) by 3 which ultimately gives us the value of y.
(2x-6)/3=y

Jeffrey Jordon

Expert2021-12-30Added 2575 answers

Subtract 2x from both sides of the equation.

$-3y=6-2x$

Divide each term by -3 and simplify.

Divide each term in -3y=6-2x by -3

$\frac{-3y}{3}=\frac{6}{-3}+\frac{-2x}{-3}$

Cancel the -3 common factor.

$y=\frac{6}{-3}+\frac{-2x}{-3}$

Each term should be simplified.

$y=-2+\frac{2x}{3}$

karton

Skilled2021-12-30Added 439 answers

Explanation:

You must do the same action on both sides of the = sign;

Therefore: